Encountering craft : methodological approaches from anthropology, art history, and design - Bose, Chandan; Mohsini, Mira (New York : Routledge, 2023)
"This book reflects on the methodological challenges and possibilities encountered when researching practices that have been historically defined and classified as 'craft.' It fosters an understanding of how methodology, across disciplines, contributes to analytical frameworks within which the subject-matter of craft is defined and constructed. The contributions are written by scholars whose work focuses on different craft practices across geographies. Each chapter contains detailed case study material along with theoretical analysis of the research challenges confronted. They provide valuable insight into how methodologies emerge in response to particular research conditions and contexts, addressing issues of decolonization, representation, institutionalization, and power. Informed by anthropology, art history and design, this volume facilitates interdisciplinary discussion and touches on some of the most critical issues related to craft research today"--
Introduction -- Critical Cloth: The Contemporary Toile de Jouy Print as Postcolonial Critique in Art and Design -- Craft, relationality, history: Wood furniture-making in mid-twentieth century Japan -- Narrating indigo: Telling and re-telling subjectivities of craft in India -- Disentangling history and practice in the weaving and dyeing course at Kyoto City University of Arts -- Prolegomena for World War I craft therapy for American injured soldiers and Reconstruction Aides -- Theorising Indigenous art practice, practicing Indigenous art theories: Māori weaving as research methodology -- Negotiating Apprenticeship: Praxis and Strictures of a Craft Practice -- 'Writing Practices' and Writing 'Practices': Observation and struggle in fieldnotes about artisanal work -- Coda.
Keywords: Folk art -- Research; Decorative arts -- Research; Handicraft -- Research; Design -- Research; Ethnic art -- Research; Material culture -- Research; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Anthropology / Cultural